Social-Economic Dynamics in the Fourth Industrial Revolution: Analysis of Its Influence on SMEs, Employment, and Poverty in the Context of Digital Society - Al Hidayat, Rahmat; Raharjo, Itot Bian; Yani, Ahmad (PT. LITERASI SAINS NUSANTARA, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of economies in many countries. The Fourth Industrial Revolution brings significant changes in how MSMEs operate, including in marketing, production, and interaction with customers. These changes can have positive or negative impacts depending on how well MSMEs adapt to new technologies. This study aims to analyze the influence of the Fourth Industrial Revolution on MSMEs, employment, and poverty in the context of a digital society, providing better insights for decision-makers in designing policies and strategies for a future economy that is sustainable and inclusive. This research uses a qualitative approach in literature review with a focus on the research contributions to community engagement. Data for the literature review were obtained through Google Scholar with a range of years from 2017 to 2024. The study results show that the Fourth Industrial Revolution has globally transformed businesses, employment, and poverty through digital technologies such as artificial intelligence, the Internet of Things, cloud computing, and robotics. Although it provides opportunities for MSMEs to thrive, challenges related to technology adoption remain. Investments in human resources, technology, and digital connectivity are crucial. Changes in workforce demands and economic inequalities underscore the need for investments in education, training, and flexible regulations.